2022
DOI: 10.1177/11297298221095769
|View full text |Cite
|
Sign up to set email alerts
|

The clinical journey and healthcare resources required for dialysis access of end-stage kidney disease patients during their first year of hemodialysis

Abstract: Background: Creation and maintenance of dialysis vascular access (VA) is a major component of healthcare resource utilization and cost for patients newly started on hemodialysis (HD). Different VA format arises due to patient acceptance of anticipatory care versus late preparation, and clinical characteristics. This study reviews the clinical journey and resource utilization required for different VA formats in the first year of HD. Method: Data of patients newly commenced on HD between July 2015 and June 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Delayed or failed AVF maturation increases the CVC dependence days and also the risk of central vein stenosis in longer term 7,13 . In addition, patients with failed AVF creation underwent significantly more CVC exchange/reinsertion and incurred higher economic burden 14 . Prior studies reported various methods to promote AVF maturation including far‐infrared energy, 15 intra‐operative flow measurement, 16 intermittent compression therapy during early post‐operative period, 17,18 and ultrasound‐guided cannulation for early phase matured AVFs 19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed or failed AVF maturation increases the CVC dependence days and also the risk of central vein stenosis in longer term 7,13 . In addition, patients with failed AVF creation underwent significantly more CVC exchange/reinsertion and incurred higher economic burden 14 . Prior studies reported various methods to promote AVF maturation including far‐infrared energy, 15 intra‐operative flow measurement, 16 intermittent compression therapy during early post‐operative period, 17,18 and ultrasound‐guided cannulation for early phase matured AVFs 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…7,13 In addition, patients with failed AVF creation underwent significantly more CVC exchange/reinsertion and incurred higher economic burden. 14 Prior studies reported various methods to promote AVF maturation including far-infrared energy, 15 intra-operative flow measurement, 16…”
Section: Functional Maturationmentioning
confidence: 99%